Community Versus Hospital Opioid-Related Overdose Deaths in Illinois. (March 2022) - Feinglass, Joe; Walker, Garth; Khazanchi, Rushmin; Rydland, Kelsey; Tessier, Robert Andrew; Mason, Maryann
Objective: To better understand approaches to reducing mortality from the opioid epidemic, we analyzed in-hospital versus community opioid-related overdose deaths in Illinois. Methods: We used data from the Statewide Unintentional Drug Overdose Reporting System (July 2017 through December 2018) to identify deaths that occurred in hospitals and communities (ie, homes or public spaces). We used census tract–level data for 34 Illinois counties to create bivariate mapping by overdose death rates. We used logistic regression to analyze the association of demographic and overdose characteristics with the likelihood of death in a hospital versus a community. Results: During the study period, 2833 opioid-related overdose deaths occurred in 24 Illinois counties, 655 (23.1%) of which occurred in the hospital; of 2178 community deaths, 1888 (86.7%) occurred in the same census tract as the decedent's recorded residence and 1285 (59.0%) occurred in the decedent's home. Non-Hispanic Black people were 1.63 (95% CI, 1.27-2.10) times more likely than non-Hispanic White people to die in a hospital. Decedents from suburban Cook County and other Chicago suburban counties were significantly more likely to die in the hospital than decedents from Chicago or other Illinois counties. Documentation of a previous overdose, history of opioid use, and having bystanders present were significantly associated with hospital deaths. Evidence of a rapid overdose, fentanyl present, or prescription opioids were significantly associated with deaths in a community. Conclusions: The high number of opioid-related overdose deaths in the community illustrates the need to decriminalize illicit drug use and facilitate treatment seeking. Establishing supervised safe consumption sites may have the biggest effect in reducing the number of opioid-related overdose deaths.